DESIGNING THE SYSTEM FOR RECEIVING ORDERS, OR SALES AT U.D. GEMILANG UTAMA - Hery Sulistyanto; Hariyanto Hariyanto, S.Kom., MMSI (Jurnal Sistem Informasi, 1998)
The purpose of designing the system for receiving orders and sales, which designed the system for receiving and re-sales of existing into a new system using a computer. on the system for receiving orders and sales of long daily activities are still done manually. From the observation that writing done, where orders received by the sales field is then handed goto the administrative orders and sales receipts each day an average sales area to receive one hundred and fifty orders. with the order then there are problems concerning the calculation of inventory, monthly reports and when there are errors in recording it must be doing a fairly complicated repairs. Of the problems that arise that may arise it is advisable to use a computer with a database system. using a computer system reports can be generated sales orders more orderly and timely sales reports every month. report in order items must be returned at anytime if needed and facilitate the recording of sales in support of this it must provide information to customers about the types of goods available and their price and the item code and notify you when you change the codes. in customer ordering code list requisitioned to facilitate data entry order